Synchronization of fractional-order discrete-time chaotic systems by an exact delayed state reconstructor: Application to secure communication - Djennoune, Said; Bettayeb, Maamar; Al-Saggaf, Ubaid Muhsen (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the synchronization of fractional-order chaotic discrete-time systems. First, some new concepts regarding the output-memory observability of non-linear fractional-order discrete-time systems are developed. A rank criterion for output-memory observability is derived. Second, a dead-beat observer which recovers exactly the true state system from the knowledge of a finite number of delayed inputs and delayed outputs is proposed. The case of the presence of an unknown input is also studied. Third, secure data communication based on a generalized fractional-order Hénon map is proposed. Numerical simulations and application to secure speech communication are presented to show the efficiency of the proposed approach.
Keywords: fractional-order discrete time systems; chaotic map; chaotic synchronization; dead-beat observer; secure data communication